PENGARUHPENGGUNAAN MIND MAPPING BERBANTUAN MINDOMO SOFTWARE TERHADAP PENINGKATAN PEMAHAMAN KONSEP PADA MATA PELAJARAN TEKNOLOGI INFORMASI DAN KOMUNIKASI - Purwoto, Krisna Mukti (2014)
Penelitian ini berangkat dari pokok permasalahan mengenai "Bagaimana pengaruh penggunaanmind mappingberbantuanmindomosofwareterhadappeningkatanpemahamankonsepsiswa pada mata pelajaran TIK (teknologi informasi dan komunikasi)". Masalah tersebut dapat dijabarkan kedalam rumusan yang lebih khusus yaitu: 1). Apakah terdapat peningkatan pemahaman konsep aspek menerjemahkan melalui penggunaan mind mappingberbantuan mindomo sofwarepada mata pelajaran TIK di SMP Negeri 1 Lembang?; 2). Apakah terdapat peningkatanpemahaman konsep pada aspek interpretasi melalui penggunaan mind mappingberbantuan mindomo sofwarepada mata pelajaran TIK di SMP Negeri 1 Lembang?; dan 3. Apakah terdapat peningkatanpemahaman konsep pada aspek ekstrapolasi melalui penggunaan mind mappingberbantuan mindomo sofwarepada mata pelajaran TIK di SMP Negeri 1 Lembang ?. Padapenelitianinimenggunakan metode kuasi eksperimen dengan desain penelitian pre-test-post-testcontrol group design. Intrumenpenelitianyang digunakanadalahsoalpre-testdanpost-testberupa 40soalpilihanberganda yang digunakanuntukmengukurpeningkatanpemahamankonsepsiswapadaaspekmenerjemahkan, menginterpretasidanmengekstrapolasi.Populasipenelitianyaitusiswakelas VIIISMP Negeri 1 Lembangdengansampelpenelitiansiswakelas VIII-B sebagaikelaseksperimendansiswakelaskelas VIII-Esebagaikelaskontrol, dengansampel yang diambildarimasing - masingkelasberjumlah 26 orang siswa. Dari temuanhasilpenelitianmenunjukanbahwanilai rata - rata post-testpemahamankonsepsiswapadakelaseksperimenyaitu 8,00lebihtinggidibandingkannilai rata - rata post-testpemahamansiswapadakelaskontrolyaitu 7,04.Sehinggadapatdisimpulkanbahwapenggunaanmind mappingberbantuanmindomosofwarememilikipengaruh yang signifikanterhadappeningkatanpemahamankonsepsiswapadamatapelajaranteknologiinformasidankomunikasi. This study departs from the subject matter of the "How does the use of mind mapping software aided Mindomo towards an improved understanding of the concept of students in the subjects of ICT (information and communication technology)". These problems can be translated into more specific formulation, namely: 1). Is there an increased understanding of the concept of translating aspects through the use of mind mapping software Mindomo aided in ICT subjects in SMP Negeri 1 Lembang?; 2). Is there an increased understanding of the concept of the aspects of interpretation through the use of mind mapping software Mindomo aided in ICT subjects in SMP Negeri 1Lembang?; and 3. Was there an increase in the aspect of understanding the concept of extrapolation through the use of mind mapping software Mindomo aided in ICT subjects in SMP Negeri 1 Lembang?. In this study, using the method of quasi-experimental research design with pre-test-post-test control group design. Research instrument used is a matter of pre-test and post-test in the form of 40 multiple-choice questions are used to measure improvements in aspects of students' understanding of the concept of translating, interpreting and extrapolating. The study population is the eighth grade students of SMP Negeri 1 Lembang with sample class VIII-B as an experimental class and a class of students of class VIII-E as a control class, with samples taken from each - each class numbered 26 students. From the findings of the research showed that the value - average post-test students 'understanding of concepts in the experimental class that is higher than the 8.00 value - average post-test students' understanding of the control class is 7.04. It can be concluded that the use of mind mapping software aided Mindomo have a significant effect on the improvement of students' understanding of concepts in the subjects of information and communication technology.